Writing Off: Approaching Modernity through Social Change - Phuyal, Komal Prasad (Tribhuvan University Journal, 2022)
As rupture in the prevailing practices, modernity adopts writing off as one of its diverse ways of bringing the ethos of contemporary time to match up with the aspirations of people. The inner core of the society develops erroneous aspects in its structural foundations over a course of time, whereby promoting social inequalities. Often, the proponents of such system fail to see through the possible implications of such fault line during the inceptions. The fissures in system set onto trouble the people, thereby obstructing the smooth functioning of the society. In such context, the society calls for the intervention of the larger agency, capable of enforcing and sustaining change. The present study examines and analyse slavery as the system that has undergone such change in the history of Nepal. I have taken Chandra Shumsher’s 1924 speech on abolition of slavery and Madan Mani Dixit’s Madhavi (1983) as the primary source of data to explore examine and analyse slavery from the intersection of history and literature in that both Shumsher and Dixit reflection the nature and course of slavery as such. Using the critical perspective of new historicism, the study concludes that modernity employs ‘writing off’ as one of the chief strategies to upgrade the polity with the ethos of contemporaneity.